Anti-Branding in the American Society and Fiction - Aslam, Saiyma; Aslam Khattak, Aiman (The Journal of Humanities & Social Sciences, 2023)
Corporatization and branding of the world seem to be a relatively new phenomenon for many people. However, they have been present for quite some time. The only difference could be found in their immensity and manifestations during the modern and postmodern times. Branding could take on a lot of different forms, like place branding, identity branding, cultural branding, nation branding, and so on. Whatever form it may assume, it has always tended to attain strongholds around us. Modern branding started in the United States somewhere around the 1920s, rose to its peak in the 1950s and then slowly met its decline till the end of the 1990s after which its focus was shifted on to the Third World. This article aims at tracing out the various socio-cultural or political factors or elements that contributed towards the Antibranding Activism aroused among the target victims of the brands themselves particularly in the United States of America. The anti-branding and anti-corporate rage has been displayed, as unfolded by Naomi Klein, by a backlash of target consumer masses via riots, denial of the branded products, reclamation of unbranded space and vice versa. The same anti-branding rage reflected in the American fiction is analysed here in selected fiction of Don Delillo